Effects of prescribed fire on botanical composition, soil cover, and forage production in Caucasian bluestem-infested rangeland in the Kansas Smoky Hills - Ramirez, Micke Paul (Kansas State University, 2021)
The spread of old-world bluestem species (Bothriochloa spp.) throughout the central and southern Great Plains poses a significant risk to native rangelands. The objective of this experiment was to evaluate the effectiveness of late-summer prescribed fire for reducing Caucasian bluestem (Bothriochloa bladhii) stands in native mixed-grass prairie and subsequent effects on soil cover, botanical composition, and forage biomass production. A mixed-grass prairie pasture with a heavy infestation of Caucasian bluestem was divided into 4,047-m² plots (n = 18) for this experiment. Plots were grouped into pairs and pairs assigned randomly to 1 of 2 treatments: no burn (n = 6), or burn (n = 12). Caucasian bluestem frequency, soil cover, and vegetative composition were measured along permanent 50-m transects in each plot, pre- and post-treatment. Forage biomass was estimated by clipping vegetation within three 50 × 50-cm frames per plot. Prescribed fire was applied on 14 August 2019. One and two years post-treatment, bare soil was greater (treatment × time; P < 0.01) in burned plots compared with non-burned plots. In contrast, litter cover was greater (P < 0.01) in non-burned plots compared with burned plots in years one and two post-treatment. Basal vegetation cover did not differ (P > 0.19) between burned and non-burned plots in either post-treatment year. Proportions of basal cover of native (P = 0.54) and introduced grasses (P = 0.10) were not different between treatments. the Conversely, proportion of basal cover attributable to all grasses decreased (treatment main effect; P < 0.01) in burned plots while remaining unchanged in non-burned plots. In years one and two post-treatment, basal cover of Caucasian bluestem was reduced (P < 0.01) by approximately 38% and 27%, respectively, compared with initial measurements. This trend was associated with less (treatment main effect; P < 0.01) forage biomass post-treatment in burned plots compared with non-burned plots. Proportions of total basal cover of all forbs and perennial forbs were greater (treatment main effect; P < 0.01) in burned plots than in non-burned plots; moreover, grass species richness was greater (treatment × time; P < 0.01) in burned plots compared with non-burned plots. Forb richness was greater (P < 0.01) in burned plots than in non-burned plots in year one post-treatment only. These data were interpreted to suggest that application of late-summer prescribed fire may be an effective means of reducing Caucasian bluestem frequency while increasing native plant richness.
Keywords: Caucasian bluestem; Plant diversity; Prescribed fire